Volume 5: Ocean Engineering; CFD and VIV 2012
DOI: 10.1115/omae2012-84177
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Use of Reduced Order Models for Unsteady Fluid Dynamic Analysis of Flexible Structures

Abstract: Reduced order models (ROMs) are computationally efficient techniques, which have been widely used for predicting unsteady aerodynamic response of airfoils and wings. However, they have not been applied extensively to perform unsteady fluid dynamic analysis of flexible structures in civil engineering. This paper discusses the application of reduced order computational fluid dynamics (CFD) model based on the eigensystem realization algorithm (ERA) in the aerodynamic analysis of flexible structures with arbitrary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, to tbe best of the authors' knowledge, this technique is relatively new in the analysis of civil engineering structures. The authors have recently presented the results of ERA based ROM for a long span bridge with and without guide vanes [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, to tbe best of the authors' knowledge, this technique is relatively new in the analysis of civil engineering structures. The authors have recently presented the results of ERA based ROM for a long span bridge with and without guide vanes [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of the authors’ knowledge, this technique is almost new in the analysis of civil engineering structures. The authors have recently showed the results of ERA-based aerodynamic ROM for a long-span bridge with and without guide vanes (Ebrahimnejad et al , 2012). Also, this procedure has been successfully applied to a bridge section and two simple canonical sections with the same chord length in Ebrahimnejad et al (2014a) and three super long-span bridges in Ebrahimnejad et al (2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Also, this procedure has been successfully applied to a bridge section and two simple canonical sections with the same chord length in Ebrahimnejad et al (2014a) and three super long-span bridges in Ebrahimnejad et al (2014b). This work develops the method proposed in Ebrahimnejad et al (2014a, 2012, 2014b) to perform aeroelastic analysis by coupling a pertinent aerodynamic ROM and compatible reduced DOF structural system.…”
Section: Introductionmentioning
confidence: 99%